Starstruck in the Promised Land : How the Arts Shaped American Passions about Israel - Goldman, Shalom (Book collections on Project MUSE., 2019)
"This cultural history of the American-Israeli relationship, beginning in the nineteenth century and going through 1947, when the state of Israel was established, to the present puts a focus on religion, Christian and Jewish, and its connections with individual American artists and their intense relationships with Israel. In high relief are the ... revealing and often little-known stories of individual writers, thinkers, and superstar performers in music, theater, dance, film, and television and their relationships"--